Migration and remittances in Central America: New evidence and pathways for future research - Ambler, Kate (International Food Policy Research Institute, 2019)
Emigration from the countries of Central America has evolved since the 1960s from small numbers of largely intra-regional emigrants to substantial numbers of people, emigrating in large part to the United States. For example, in 1960, 69 percent of emigrants from El Salvador resided in Honduras and only 12 percent lived in the United States. By 2000, 88 percent of Salvadoran emigrants in the world lived in the United States.